Liquidity, Size and Financial Performance of Deposit Money Banks in Nigeria - Aliyu, Almustapha Alhaji`; Ali, Adamu Yusuf; Jaob, Lapips Caleb; Mohammed, Halima Sadiya (Kashere Journal of Management Sciences, 2024)
This study examines the impact of liquidity and size on financial performance of deposit money banks (DMBs) in Nigeria. The data for the study were collected from the annual reports and accounts of all DMBs quoted in the Nigeria Stock Exchange within the period of 2007 and 2016. OLS regression and correlation analysis were used to test the hypotheses in addition to some diagnostic tests conducted on the data. The results of the study revealed that the both liquidity and size have significant positive impact on Return on Asset and Return on Equity. The study recommends that DMBs in Nigeria should work toward improving management of their liquidity and total asset to enhance their financial performance.